Verify that: (a-b) - c ≠ a - (b-c) where, a = 5/3, b= 11/2, c= -9/4
Attachments:
![](https://hi-static.z-dn.net/files/d5d/71552bd242f1ed31fde8568d9ebd7fce.jpg)
Answers
Answered by
5
this is your answer hope it helps u
Attachments:
![](https://hi-static.z-dn.net/files/d32/7e732b7374289247034cb8897a659199.jpg)
![](https://hi-static.z-dn.net/files/d92/66c9931750c98249c2cd5f78c4582931.jpg)
Answered by
6
Answer:
(a-b)-c ≠a-(b-c)
*●=[(5/3-11/3)]-(-9/4)≠(5/3)-[11/2-(-9/4)]
=-23/6-(-9/4)
=-19/12
●(5/3)-[11/2-(-9/4)
=5/3-31/4
=-23/12
●-19/12≠-23/12 answer
i hope it's help u
if u like than mark as brainlist
Similar questions